2003
DOI: 10.4049/jimmunol.171.2.733
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Autoantigen-Specific Th2 and Tr1 Regulatory T Cells and Modulation of Autoimmune Diabetes

Abstract: Autoantigen-based immunotherapy can modulate autoimmune diabetes, perhaps due to the activation of Ag-specific regulatory T cells. Studies of these regulatory T cells should help us understand their roles in diabetes and aid in designing a more effective immunotherapy. We have used class II MHC tetramers to isolate Ag-specific T cells from nonobese diabetic (NOD) mice and BALB/c mice treated with glutamic acid decarboxylase 65 peptides (p206 and p221). Based on their cytokine secretion profiles, immunization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
85
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 61 publications
(82 reference statements)
6
85
2
Order By: Relevance
“…8B). Consistent with our previous studies using T cells isolated from p221-immunized NOD mice, these results suggest that the migration of diabetogenic T cells into pancreatic islets was blocked by N221 ϩ cells (20). Therefore, these N221 ϩ T cells exhibit regulatory functions in vivo and efficiently prevent both insulitis and diabetes development.…”
Section: N221 ϩ Cells Protect From Adoptive Transfer Of Diabetessupporting
confidence: 80%
See 4 more Smart Citations
“…8B). Consistent with our previous studies using T cells isolated from p221-immunized NOD mice, these results suggest that the migration of diabetogenic T cells into pancreatic islets was blocked by N221 ϩ cells (20). Therefore, these N221 ϩ T cells exhibit regulatory functions in vivo and efficiently prevent both insulitis and diabetes development.…”
Section: N221 ϩ Cells Protect From Adoptive Transfer Of Diabetessupporting
confidence: 80%
“…The p221 peptide has been identified as one of the most dominant epitopes derived from the GAD protein and may play an important role in diabetes development (19,26). We have previously shown that immunization of NOD mice with p221 could activate p221-specific regulatory T cells, leading to the suppression and delay of diabetes development (20). In this report we provide evidences demonstrating that T cells specific for p221 are present in unimmunized naive NOD mice.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations